PENGGUNAAN ALAT PERMAINAN EDUKATIF (APE) UNTUK MENDUKUNG PERKEMBANGAN ANAK USIA 5-6 TAHUN DI PAUD AL FIKRI - Rahma, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract                                                                                                                          Educational Game Tools are very important to be used to support the development of children so that they able to sharpen their skills because children learn from real or concrete objects. The method used in this research is descriptive and using qualitative research approach. The technique used in this research are interview v, observation and documentation. Research subjects were group B teachers and children aged 5-6 years in PAUD Al Fikri North Pontianak. From the results of this research and discussion of this research, we can take conclusion that is 1) the availability of educative game tools to support the development of children aged 5-6 years in PAUD Al Fikri North Pontianak is quite good although there are still some educational game tools that are not available. 2) the use of educational game tools to support the development of children aged 5-6 years in early childhood Al Fikri North Pontianak is good because the teachers are following the procedures of media usage includes the preparation stage, implementation, evaluation and follow-up. 3) Educational game tools used in early childhood Al Fikri are able to support the development children aged 5-6 years.Keywords: Educational Game Tools, Children Development